Bioactive Compounds Content and Pharmacological Activities of Chili Pepper (Capsicum Sp.) - Swastiari Dwi Yanti; Warsi Warsi (Universitas Muhammadiyah Malang, 2021)
Chili pepper (Capsicum sp.) is an essential spice belonging to the Solanaceae family. Chili pepper is consumed as a food source, additive in the food industry, and necessary medicine. Chili pepper is rich in nutrients and secondary metabolites to generate new bioactive compounds. Chili pepper fruit contains bioactive compounds including alkaloids, capsaicinoid, carotenoids (anteraxanthin, β-carotene, capsanthin, violaxanthin, β-cryptoxanthin, zeaxanthin, lutein epoxide, capsorubin, and neoxanthin), peptides (defensin, thionin-like peptide), phytol, fatty acids (myristic acid, methyl stearic, methyl linoleic), phenolic (chlorogenic acid) and flavonoids (quercetin, luteolin, rutin). The compounds in chili pepper constitute a bioactive source that acts as an antioxidant, antimicrobial, antifungal, anti-inflammatory, anti-obesity, anti-diabetic, and dyslipidemia. This review intends to describe the content of bioactive compounds that are very beneficial for health. This review is expected to increase chili consumption and its application in the food industry